Evaluation of the Preventive Effectiveness of Influenza Vaccines in the Epidemic Season 2019–2020 in St. Petersburg - M. K. Erofeeva; M. A. Stukova; E. V. Shakhlanskaya; Zh. V. Buzitskaya; V. L. Maksakova; T. I. Krainova; M. M. Pisareva; A. B. Popov; M. G. Pozdnjakova; D. A. Lioznov (Эпидемиология и вакцинопрофилактика, 2021)
Background. The vaccine is the best available instrument to prevent influenza and reduce the risks of major disease complications and mortality. The vaccine effectiveness during the influenza season depends on a number of factors: (1) a person vaccinated (their age and health status); (2) the vaccine formulation; (3) types and subtypes of the circulating viruses; (4) vaccination timeline, as the immune response fades over time. An influenza vaccine can yield different effectiveness in people who have been infected or vaccinated previously and in those who have not been yet exposed to the circulating viruses. At present, trivalent and quadrivalent influenza vaccines are registered and produced in Russia. It allows for vaccination of all social groups, including high-risk populations, and for increasing the number of vaccinated individuals yearly. Russian Federation constantly improves the production of influenza vaccines, introducing new variants of vaccine formulations into national clinical usage. It is thus essential to monitor and analyze the changes in the effectiveness of influenza vaccines every season.Aim of the study. To evaluate of the effectiveness of Russian domestic influenza vaccines during the epidemic season 2019–2020 in St. Petersburg compared to the season 2018–2019.Materials and Methods. 3315 female and male adult participants aged 18 years and older were monitored from October 2019 to March 2020. The group included university students and tutors, researchers, and production and office workers of industrial enterprises. Sovigripp, Grippol Plus, Ultrix, and Ultrix Quadri influenza vaccines were used for immunization.Results and Discussion. In the context of incomplete correspondence between the viruses circulating in Russia and the strains used in the vaccines, the vaccination of the St. Petersburg population during the epidemic season 2019-2020 with Sovigripp, Grippol Plus, Ultrix, and Ultrix Quadri influenza vaccines cumulatively reduced influenza and ARI incidences by half; the total vaccine effectiveness against influenza and ARI amounted to 50.0%. The strongest preventive effect was identified for Grippol Plus, Ultrix, and Ultrix Quadri which demonstrated the total vaccine effectiveness from 70.6% to 75.0%, and their effectiveness against influenza A and B viruses reached from 65.5% to 83.5%.Conclusion. In the context of incomplete correspondence between the viral strains used in the vaccines and the strains circulating in Russia and St. Petersburg during the epidemic season 2019- 2020 and considering the active circulation of non-influenza viruses such as rhinoviruses and adenoviruses, we found a moderate preventive effectiveness of the influenza vaccines during the seasonal epidemic increase in ARI cases. Russian domestic influenza vaccines were shown to have good acceptability, be safe, and non-reactogenic.